Distal brachial artery embolization for the treatment of dialysis access steal syndrome - Brian M. Leoce; Helen S. Wei; Steven M. Hadley, Jr.; Kevin Z. Molnar; Joe T. Huang; Michael A. Curi (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Dialysis access steal syndrome (DASS), first reported in 1969, describes arterial insufficiency occurring after the creation of an arteriovenous (AV) anastomosis for dialysis access Storey et al. (1969). The overall incidence of symptomatic steal syndrome ranges from 0.25% to 1.8% in forearm autogenous AV access, with a higher incidence in prosthetic AV access (Morsy et al., 1998; Padberg et al., 2008). Severe DASS symptoms are more likely to occur with brachial artery AV access, with a reported incidence of 4 to 9% (Padberg et al., 2008). Endovascular treatment of DASS in radial artery-based access has been described using coil embolization of the radial artery distal to the AV anastomosis (Plumb et al., 2008; Shukla et al., 2012; Miller et al., 2008; Alabi et al., 2016). Despite its reported successes for the treatment of forearm access related DASS, coil embolization for the treatment of steal syndrome associated with brachial artery dialysis access has not been reported. Here we describe the first three cases of DASS successfully treated with coil embolization of the distal brachial artery. All patients experienced complete resolution of their symptoms and remain with the functional AV access. All patients have consented to the publication and presentation of their case.